Analysis of The Implementation of Training and Coaching Programs from A Human Resource Management (SDM) Perspective in Educational Institutions - Ybnu Taufan, Muhammad (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to analyze the implementation of training and coaching programs from a Human Resource Management (HRM) perspective in educational institutions. The research was conducted among junior high school teachers (SMPN) in Mamuju Regency, involving a total population of 125 teachers. Using purposive sampling, 50 teachers who had participated in training and coaching programs were selected as research participants. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using thematic analysis techniques, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of competency-based training and coaching programs contributes significantly to improving teachers’ pedagogical and professional competencies. Teachers reported positive changes in instructional planning, classroom management, and the integration of learning technologies. From an HRM perspective, the programs functioned as strategic tools for professional development, performance enhancement, and capacity building. Supporting factors included institutional commitment, leadership support, and collaborative work culture, while constraints involved limited time allocation and workload pressures. The study concludes that structured training and continuous coaching serve as effective HRM strategies in enhancing teacher performance within educational institutions. The findings provide practical implications for policymakers and school management in designing sustainable professional development programs.